2015
DOI: 10.1016/j.jenvp.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of frequency and mode of contact with nature on children's self-reported ecological behaviors

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: influences EB in the three conditions. The strongest total impact was found for children living in the city and the weakest for those in the work-related rural area. No direct effect of FCN on EB was found for children in the non work-related rural area, and a negative direct effect for those in the work-related rural area. A better understanding of this direct effect will be needed in order to gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 27 publications
2
84
1
5
Order By: Relevance
“…Urban children claim that nature is important for people to live, but they do it in an abstract way, for example, 'Plants give us O 2 ' (Girl,11,E1). This kind of response is also found in rural children but, in addition, they add arguments that reflect their closeness to natural environments, children's contact with nearby nature is more frequent than that of urban ones (Collado et al 2015, McCormarck 2000. Moreover, rural agricultural children seem to talk about nature more than those in the other two groups.…”
Section: For Instance 'I Think About the Animals That I Like The Vamentioning
confidence: 85%
See 2 more Smart Citations
“…Urban children claim that nature is important for people to live, but they do it in an abstract way, for example, 'Plants give us O 2 ' (Girl,11,E1). This kind of response is also found in rural children but, in addition, they add arguments that reflect their closeness to natural environments, children's contact with nearby nature is more frequent than that of urban ones (Collado et al 2015, McCormarck 2000. Moreover, rural agricultural children seem to talk about nature more than those in the other two groups.…”
Section: For Instance 'I Think About the Animals That I Like The Vamentioning
confidence: 85%
“…It is common for children to help their parents in an agricultural family business (Collado et al 2015, McCormarck 2002) and children are expected to be involved in conversations about nature in a regular basis.…”
Section: Study Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive experiences in nature, as reported by adults (Wells and Lekies, 2006; Hinds and Sparks, 2008; Larson et al, 2011b) and children (Larson et al, 2011a; Collado et al, 2015), have been positively associated with higher engagement on PEB. We define positive experiences in nature as those experiences in which the individual can engage freely with the environment (Chawla and Derr, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…A new and innovative line of research about the promotion of PEB draws on the hypothesis that direct contact with nature is positively associated with pro-environmental attitudes and PEB (Larson et al, 2011a; Chawla and Derr, 2012; Cheng and Monroe, 2012; Collado et al, 2015; Otto and Pensini, 2017; Whitburn et al, in press). In line with this, it has been suggested that reducing opportunities to have contact with nature can lead to an amplified feeling of human-nature dissociation (Chawla and Derr, 2012), which may, in turn, hinder support for environmental causes (Soga and Gaston, 2016).…”
Section: Introductionmentioning
confidence: 99%